2005
DOI: 10.1007/s00404-005-0041-y
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized, double-blinded, placebo-controlled trial of preoperative rofecoxib for pain relief in uterine curettage

Abstract: The preoperative administration of rofecoxib was not effective in reducing pain in uterine curettage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…However, the combination of intrauterine anesthesia and naproxen sodium has been shown to have a promising effect on pain reduction. In addition to the study by Poomtavorn and Phupong [22], this study also reveals that there are different sources of uterine pain. We used a different type of NSAID administered rectally and were also unable to demonstrate a pain-reducing effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the combination of intrauterine anesthesia and naproxen sodium has been shown to have a promising effect on pain reduction. In addition to the study by Poomtavorn and Phupong [22], this study also reveals that there are different sources of uterine pain. We used a different type of NSAID administered rectally and were also unable to demonstrate a pain-reducing effect.…”
Section: Discussionmentioning
confidence: 99%
“…Poomtavorn and Phupong [22] administered 50 mg of rofecoxib, an NSAID, 60 min prior to uterine curettage under a paracervical bloc and were not able to demonstrate a significant pain reduction during the procedure. They also suggested that prostaglandins are not the main source of pain during the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The largest trial of NSAIDs prior to IUD insertion used ibuprofen 400 mg, a dose lower than is commonly recommended in the United States [7]. Interestingly, NSAIDs are often recommended prior to other office-based gynecologic procedures, such as colposcopy [8], endometrial biopsy [9] and dilation and curettage [10][11][12], though data are mixed about their effectiveness with these procedures as well.…”
Section: Introductionmentioning
confidence: 99%
“…Öte yandan rofekoksib, etorikoksib ve naproksen sodyum gibi NSAID'lerin analjezik etkinliğinin araştırıldığı diğer çalışmalarda, tek başına kullanıldıklarında NSAİD'lerin plaseboya göre anlamlı etkilerinin gözükmediği saptanmıştır (4,(19)(20)(21). Bununla beraber Doğan ve ark.…”
Section: Discussionunclassified